Effect Of Tri Ethylen Glycol (Teg) Concentration And Temperature Wet Gas Against Water Content Gas Outlet Glycol Contactor In Natural Gas Dehydration Process - Sri Martini, Kiagus Ahmad Roni, Ericson Simanungkalit, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
One of the processing units located at the Natural Gas Processing Station is the Dehydration Unit (DHU). In the Dehydration Unit, there is a Glycol Contactor column which is the place for the absorption of water content from the wet gas that enters the column. Where the material used as an absorbent (absorbent) is Tri Ethylene Glycol and the substance that is absorbed (absorbate) is water vapour (H2O). Based on the actual available data, there is an increase in water content in the sales gas (Dry Gas) of 1.47 lb / MMscf while the design is 0.05 lb / MMscf. This is because the water content in the inlet gas (wet gas) is greater than the design. namely 55.23 lb / MMscf and design 31.3 lb / MMscf. The amount of water content in wet gas and dry gas is influenced by the wet gas temperature and the concentration of Tri Ethylene Glycol (TEG). Based on the results of calculations and analysis, it can be said that the performance of the Glycol Contactor column has decreased water absorption efficiency when compared to the design.